2017
DOI: 10.1039/c6nr09182b
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic functional and architectonic heterogeneity of tumor-targeted protein nanoparticles

Abstract: Self-assembling proteins are gaining attention as building blocks for application-tailored nanoscale materials. This is mostly due to the biocompatibility, biodegradability, and functional versatility of peptide chains. Such a potential for adaptability is particularly high in the case of recombinant proteins, which are produced in living cells and are suitable for genetic engineering. However, how the cell factory itself and the particular protein folding machinery influence the architecture and function of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…Instead, T22‐GFP‐H5T tolerated well the presence of salt in the media. However, this construct showed high instability during freezing and thawing and it partially disassembled as structures smaller than 12 nm ( Figure A), of size comparable to assembling intermediates described for T22‐GFP‐H6 . Some of these structures were also observed under transmission electron microscopy (TEM) (Figure C).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Instead, T22‐GFP‐H5T tolerated well the presence of salt in the media. However, this construct showed high instability during freezing and thawing and it partially disassembled as structures smaller than 12 nm ( Figure A), of size comparable to assembling intermediates described for T22‐GFP‐H6 . Some of these structures were also observed under transmission electron microscopy (TEM) (Figure C).…”
Section: Resultsmentioning
confidence: 71%
“…Such fusion protein is composed by T22, a potent ligand of the cell surface cytokine receptor CXCR4, overexpressed in several metastatic human cancers, a fully fluorescent GFP and a C‐terminal polyhistidine tail. T22‐GFP‐H6 spontaneously self‐assembles in physiological conditions as 12 nm nanoparticles, formed by around ten copies of the polypeptide, organized in a toroid architecture and with some extent of structural flexibility . The high selectivity of T22 for CXCR4 observed in cell culture is fully kept in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Treating the material with SDS resulted in monomers of 5.5 nm (Figure C), which represented the probable building blocks of the nanoparticles. In the related self‐assembling protein T22‐GFP‐H6, in which the sizes of the building block and the assembled version are both equivalent to those of T22‐mRTA‐H6, the use of small‐angle X‐ray scattering and other sophisticated analytical methods as well as in silico modeling have revealed that the nanoparticle was formed by ≈10 monomers. Being estimative, this figure also fits to T22‐mRTA‐H6.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, by preserving the native state of the samples it may also conserve antigenicity due to less altered peptides and proteins, getting a higher labeling in less artifacted nanomaterials that allows the obtaining of robust quantitative and qualitative data . Recently, several biomaterials, nano‐ and micro‐structures with drug delivery and antimicrobial interest have been characterized by localizing a wide variety of peptides or proteins . However, no specific studies of these new materials have ameliorated imaging techniques for the localization of antigens at nanoscale level.…”
Section: Resultsmentioning
confidence: 99%
“…So, rapid and cheap methods such as ours may be applied for the adequate characterization of complex molecules and their future commercialization. Although, in this study, we have evaluated the efficiency of the newly developed protocols with protein‐based aggregates, the study of peptides and proteins in a wide plethora of presentations at nanoscale such as self‐assembling nanoparticles, bioinspired proteosomes, dendrimers, micelles, scaffolds, nanocomposites, coiled‐coils, and vault nanocapsules, among others, could be substantially improved with these two new approaches. Although more specific studies are necessary, the results presented here focused on the use of general methods as a first screening of samples but with the mind in specific protocols to obtain best possible localization of peptides and proteins in a wide variety of samples.…”
Section: Resultsmentioning
confidence: 99%